Study of a contracted glow in low-frequency plasma-jet discharges operating with argon - Minotti, Fernando Oscar (2015)
In this work, we present an experimental and theoretical study of a low frequency, atmospheric plasma-jet discharge in argon. The discharge has the characteristics of a contracted glow with a current channel of submillimeter diameter and a relatively high voltage cathode layer. In order to interpret the measurements, we consider the separate modeling of each region of the discharge: main channel and cathode layer, which must then be properly matched together. The main current channel was modeled, extending a previous work, as similar to an arc in which joule heating is balanced by lateral heat conduction, without thermal equilibrium between electrons and heavy species. The cathode layer model, on the other hand, includes the emission of secondary electrons by ion impact and by additional mechanisms, of which we considered emission due to collision of atoms excited at metastable levels, and field-enhanced thermionic emission (Schottky effect). The comparison of model and experiment indicates that the discharge can be effectively sustained in its contracted form by the secondary electrons emitted by collision of excited argon atoms, whereas thermionic emission is by far insufficient to provide the necessary electrons.